The Athena Study: 12 Months Safety and Efficacy Data for Everolimus Combined with Tacrolimus or Cyclosporine Compared to a Standard Tacrolimus-Mycophenolate Regimen in de Novo Kidney Transplant Patients. (July 2018) - Nashan, Björn; Sommerer, Claudia; Suwelack, Barbara; Dragun, Duska; Hauser, Ingeborg A; Witzke, Oliver; Hugo, Christian; Kamar, Nassim; Merville, Pierre; Schenker, Peter; Junge, Martina; Thaiss, Friedrich
Abstract : Athena Study Group. Background: The ATHENA study was set up to compare efficacy and safety of everolimus [EVR] combined with tacrolimus [TAC] or cyclosporine A [CyA] vs. a mycophenolic acid [MPA] with TAC standard regimen in de novo kidney transplant [KTx] recipients. Methods: In this 12 months [M] prospective, open-label, multi-center study 612 patients [pts] were randomized 1:1:1 at time of Tx to either EVR (target trough: 3-8ng/ml M1-M12) + TAC (target trough: 4-8ng/ml M1-M3; and 3-5ng/ml M3-M12), or EVR (3-8ng/ml M1-M12) + CyA (target trough: 75-125ng/ml M1-M3; and 50-100ng/ml M3-M12) or TAC (target trough: 4-8ng/ml M1-M3; and 3-5ng/ml M3-M12) + MPA, all with steroids. Here we report M12 efficacy and safety data from 208 EVR+TAC, 199 EVR+CyA and 205 TAC+MPA treated pts. Results: Treated BPAR events occurred in 6.7% of EVR+TAC pts vs 17.6% of EVR+CyA and 3.9% of TAC+MPA pts. Most of these events were graded mild, classified as BANFF IA: 1.9% vs 9% vs 1.5%, respectively; only few BANFF IIB/III occurred with 1.5% vs 2% vs 0.5% per group, respectively. Only few patients died during study period: 5 pts in EVR+TAC, 5 in EVR+CyA and 6 in TAC+MPA group. Incidence of graft loss was overall small: 4.8% (10 pts) in EVR+TAC vs 6.5% (13pts) in EVR+CyA and 2.9% (6pts) in TAC+MPA group - including 5 primary non-functioning grafts in each EVR-group and 1 in TAC+MPA group. Safety profiles of the three regimen were comparable: the incidence of AEs or infections leading to study drug discontinuation or dose adjustment/interruption were 56.7% in EVR+TAC, 55.5% in EVR+CyA vs 61.3% in TAC+MPA arm. These discontinuations or pausing [d/p] of study drug application were driven mainly by infections (as reasons for d/p: 15.2%EVR+TAC, 10.1%EVR+CyA, 31.3%TAC+MPA) and leukopenia (as reasons for d/p: 1.9%EVR+TAC, 3.0%EVR+CyA vs.10.8%TAC+MPA; p<0.01). Total incidence of leukopenia under treatment was 8.6% in EVR+TAC, 6.6% in EVR+CyA vs 19.1% for TAC+MPA (p<0.01). There were no differences on wound healing seen from incidences of AEs on wound complications, such as wound dehiscence, wound complications or impaired healing, with summed up incidences as follows: 41.9% EVR+TAC, 38.9% EVR+CyA, 43.2% TAC+MPA. No difference in proteinuria was seen, incidence of nephrotic proteinuria was 1.3% in EVR+TAC vs 0.7% in EVR+CyA and 3.7% in TAC+MPA treated patients. Conclusion: ATHENA as to date largest prospective randomized European KTx study confirmed good efficacy and event rates within international standards for all 3 groups. There were no unexpected safety events for the patient population studied herein. Of note, there were no differences in reported AEs on wound healing, no differences in proteinuria but less leukopenia and fewer infections with EVR-based regimens.